Incorporation of tio2 and Tio2-Ag Nanoparticles in Recycled High-Density Polyethylene: Effect of the Type of Photocatalyst and Incorporation Method on Photocatalytic Activity for the Decomposition of No - Carbonnel-Torralbo, A; Zapata-Ramirez, P; Gavilanes-Ruiz, D; Loyo-Davila, C; Saavedra-Gonzalez, M (Springer, 2024)
This work reported two types of photocatalysts in polymeric sheets derived from recycled high-density polyethylene (HDPEr): anatase TiO2 and Ag-decorated anatase TiO2 (TiO2-Ag). The Ag nanoparticles were deposited on the TiO2 nanoparticles via chemical reduction using formaldehyde as the reducing agent, although XPS analysis indicated that anatase was also reduced during Ag deposition. The sheets were prepared using two methods: extrusion and a plasma immersion process. In the first one, nanoparticles were introduced during extrusion, resulting in photocatalyst/HDPEr composites. On the other hand, the plasma method involved depositing photocatalyst nanoparticles into the polymer sheet surface through a two-step process of air plasma treatment followed by immersion in an aqueous photocatalyst suspension. The composites obtained through extrusion exhibited a higher Young’s modulus compared to neat HDPEr, attributed to the reinforcing effect of the nanoparticles, which was more significant with the incorporation of TiO2 nanoparticles. Photocatalytic activity assessment revealed that sheets obtained by extrusion showed poor performance, whereas photocatalyst deposition on sheets significantly enhanced NOx photodegradation. Notably, TiO2-Ag nanoparticles exhibited superior photocatalytic activity, with the polymeric sheet containing TiO2-Ag nanoparticles on the surface achieving the highest activity (~ 23.67% NOx photodegradation). The detailed methodology and robust experimental data provided offer valuable insights into optimizing nanoparticle incorporation techniques to enhance the functional properties of recycled polymeric materials for environmental applications. Overall, although the plasma treatment did not affect the mechanical properties of the sheets significantly, it allows an outstanding advance in NOX abatement. Especially for the TiO2-Ag-modified sheets. Based on this background, this research addresses a double environmental approach by developing self-cleaning building panels from HDPEr. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.